Basil of Caesarea, Didymus The Blind, and The Anti-Pneumatomachian Exegesis of Amos 4:13 and John 1:3 - DelCogliano, Mark (The journal of theological studies, 2010)
Recent scholarship has increasingly questioned the traditional assumption that Athanasius of Alexandria was a major influence upon Basil of Caesarea. This study seeks to make a concrete contribution to this debate by suggesting that Basil’s anti-pneumatomachian exegesis of Amos 4:13 and John 1:3 was influenced by Didymus the Blind rather than by Athanasius. It begins by demonstrating four parallels in the exegesis of these two verses between Basil’s Against Eunomius and Didymus’ On the Holy Spirit, and that they are not due to a common use of Athanasius. After ruling out other possible sources for Basil, it next argues that these parallels are best interpreted as indicating that Basil was influenced by Didymus rather than vice versa. If this thesis is correct, Didymus’ On the Holy Spirit needs to be dated to the late 350s or early 360s (much earlier than the date of the 370s advocated in recent scholarship), and it should prompt a reassessment of Basil’s sources and theological development.